ChemInform Abstract: Synthesis, Detailed Characterization, and Theoretical Understanding of Mononuclear Chromium(III)‐Containing Polyoxotungstates [CrIII(HXVW7O28)2] 13‐ (X: P, As) with Exceptionally Large Magnetic Anisotropy. Issue 43 (21st October 2014) - Liu, Wenjing; Christian, Jonathan H.; Al‐Oweini, Rami; Bassil, Bassem S.; van Tol, Johan; Atanasov, Mihail; Neese, Frank; Dalal, Naresh S.; Kortz, Ulrich
Abstract Compounds (IV) and (VI) are characterized in the solid state by single crystal XRD, IR spectroscopy, EPR, magnetic measurements, and DFT calculations.